FUNGSI KYARABEN PADA ANAK TAMAN KANAK-KANAK DI JEPANG - Ni Luh Ayu Aprilita; Ni Wayan Meidariani; Anak Agung Ayu Dian Andriyani (Universitas Negeri Padang, 2021)
This research examines the function of Kyaraben in kindergarten children Japan. This study aims to analyze the function of Kyaraben in Japanese kindergarten children. The data collection method used is the observation method with the data collection technique is conversation technique (interview) through zoom media to four mother Japanese informant. The research location is in Tennouji Osaka, Japan. Data analysis methods and techniques were analyzed using qualitative descriptive methods. Meanwhile, methods and techniques for presenting the results of data analysis using informal methods. Based on the results of the study, it can be seen that there are two functions of Kyaraben for kindergarten children in Japan. Kyaraben as impulse (Impuls). The function of the impulse that give the stimulus or response from the child to eat all the meal in Kyaraben. Kyaraben has an attractive, colorful display element, and there are characters that kids like. Furthermore, Kyaraben functions as manipulation (Manipulasi) so that children continue to enjoy Kyaraben even though there are foods they don't like.